Real-Time Monitoring System and IOT Smart Parking Booking (Case study: One Hotel in Tangerang) - Nadeak, Yogi Valentino; Ho, Patricia; Masriah, Masriah (PTE FTK UIN Ar-Raniry, 2024)
Since cars and motorbikes are the most popular personal mobility, public spaces must always provide enough parking for every visitor. However, occasionally there are more parking spaces available than there are guests, which makes it difficult for visitors to find an empty spot and takes a while. It can be found in the case study conducted in a hotel in Tangerang. This case study informs the development of an Internet of Things (IoT) smart parking system that uses Wi-Fi and the MQTT communication protocol to monitor user behavior, identify available parking spaces, and recognize vehicle entry. The ESP8266 microcontroller serves as the sensor node. Other sensors that are used include the RFID RC-522 sensor to determine how long a car user has been in the area, the Servo SG92R infrared (IR) sensor to detect the presence of a vehicle, and the HC-SR04 ultrasonic sensor to detect parking spaces. The outcomes showed that the Thingsboard platform's monitoring capability and the ability to reserve particular parking spaces using an MIT App Inventor app proved the smart parking system's successful implementation.